2020
DOI: 10.1093/neuros/nyaa282
|View full text |Cite
|
Sign up to set email alerts
|

How Reliable Are Volumetric Techniques for High-Grade Gliomas? A Comparison Study of Different Available Tools

Abstract: Abstract BACKGROUND Gliomas are the most common malignant primary brain tumors. Assessment of the tumor volume represents a crucial point in preoperative and postoperative evaluation. OBJECTIVE To compare pre- and postoperative tumor volumes obtained with an autom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 16 publications
0
22
0
Order By: Relevance
“…This possibility may help address concerns about overestimation of enhancing tumor volume when using BraTumIA 1.2, previously noted in preoperative patients, 15 which was confirmed in a more recent study. 16 Reliability measured by ICC, concordance measured by CCC, and overlap measured by Dice coefficients were similar between the 2 software versions.…”
Section: Discussionmentioning
confidence: 75%
“…This possibility may help address concerns about overestimation of enhancing tumor volume when using BraTumIA 1.2, previously noted in preoperative patients, 15 which was confirmed in a more recent study. 16 Reliability measured by ICC, concordance measured by CCC, and overlap measured by Dice coefficients were similar between the 2 software versions.…”
Section: Discussionmentioning
confidence: 75%
“…The Brain Tumor Image Analysis tool (BraTumIA) has been developed to segment three brain tumor compartments using four scan sequences [33,75] and has been shown to have good agreement with manual tumor volumes on preoperative scans. The Pearson's correlation coefficient between manual and BraTumIA tumor volumes was 0.8 based on 19 patients [75] and 0.88 based on 58 patients [76], albeit with a systematic overestimation. In addition, the BraTS challenge has been held yearly since 2012, which aims to improve disease diagnosis, treatment planning, monitoring, and clinical trials by means of reliable tumor segmentation.…”
Section: Discussionmentioning
confidence: 87%
“…In a recent study, manual segmentation using Horos was compared against alternative techniques and software in the assessment of pre- and post-operative tumor volumes of high-grade gliomas in humans. It was found that the manual and semi-automated software showed high agreement in preoperative volumetric assessment and were adequate for post-operative volumetric assessment ( 26 ). From this conclusion, we were confident that the software tool could be used to measure the pre- and post-operative cystic volumes accurately.…”
Section: Discussionmentioning
confidence: 99%